The Spanish Horse and the Thunder Drum: Taxidermied Subjects and Animal-Made-Objects in the Early Nineteenth Century - Mattfeld, Monica (Humanimalia, 2025)
Life for many horses at the turn of the nineteenth century was short and subject to objectification before and after death. However, the life and afterlife of one horse at Astley’s Amphitheatre, the Spanish Horse, resisted the usual loss of identity animal death often brings. In this article I first provide a biography of the Spanish Horse and then question his afterlife as a theatrical thunder drum. In doing so, I think about the nature of taxidermy, memorial, and the usual binary of subject/object inherent within fragmented animal bodies. As part of this process, I explore the thunder drum/Spanish Horse with the aid of ecofeminism, philosophies of taxidermy, and material feminist thought, and I argue that the afterlife of the Spanish Horse as a thunder drum was one of loving remembrance that did not erase the animal self within the material object. Instead, I suggest, the preservation of the Spanish Horse’s skin after death enabled his ongoing participation and agential voice within the Amphitheatre, while elevating him above other animals therein.